Changing Environment in Indian Banking Sector - B. , Neeraja; M. , Radhikaashree (International Journal of Psychosocial Rehabilitation, 2020)
There has been a dramatic transformation in the banking industry in the last few years. Digital banking, multiservices, competing global forces at lesser cost, and online transactions are now significant and ubiquitous features for banking services. There is now a move to achieve excellence in multi-dimensional aspects of the industry. To achieve this, the banking sector now strives to create an advanced business model with strategic planning, and FinTech (finance technology) offers one such business model. FinTech offers necessary help to the banking sector so as to enhance customer relations, quality of services (QoS), and customer satisfaction. This paper analyzes FinTech from various perspectives, like its offerings, such as a set of computer programs or software that enhances financial services with the help of advanced robotics, artificial intelligence (AI), enhanced cybersecurity, and customer intelligence. The paper evinces the role of FinTech as a significant provider for new entrants with its simplified operational solutions. The paper stresses the increase in FinTech implementation in terms of fine-tuning the digital efforts in the financial domain. The focus is on investments and automation through robotics on transactions and other functions like lending, clearance, settling cash, and security-related transactions.